Conservation agriculture practices improves productivity and sustainability of peanut (Arachis hypogaea)-based cropping systems - JAIN, N K; JAT, RAM A; YADAV, R S; MEENA, H N (The Indian Journal of Agricultural Sciences, 2021)
To assess the influence of conservation agriculture (CA) practices on productivity and sustainability of peanut (Arachis hypogaea L.) - based cropping systems, the present field experiment was conducted for five consecutive years (2011-12 to 2015-16) at Junagadh, Gujarat, India. The experiment, comprising 14 treatments, viz. sole peanut, peanut-Sesbania, peanut-green gram (GG), peanut-conventional tilled wheat (CTW), peanut-CTW-Sesbania, peanut- CTW-GG, peanut-CTW-wheat straw incorporation (WSI), peanut-zero tilled wheat (ZTW), peanut-ZTW-Sesbania, peanut-ZTW-GG, peanut-ZTW-WSI, peanut+pigeonpea, peanut+pigeonpea-Sesbania and peanut+pigeonpea-GG was laid out in randomized block design with three replications at fixed site. Peanut -CTW-Sesbania cropping system (2.94 t/ha) recorded maximum pod yield of peanut while haulm yield was higher under peanut-ZTW-Sesbania (3.24 t/ha). Green manuring with Sesbania in peanut-ZTW and peanut+pigeonpea recorded higher grain yield of wheat (2.91 t/ha) and sud yield of pigeonpea (1.93 t/ha), respectively. System productivity (4.55 t/ha) was significantly higher under peanut-ZTW-Sesbania cropping system over sole peanut (with or without GM), peanut-CTW/ZTW, peanut- ZTW-WSI and peanut+pigeonpea (with or without GM). Peanut-ZTW-Sesbania also recorded maximum sustainable yield index (0.46) and sustainable value index (0.48) than other cropping systems. Thus, peanut followed by ZTW or CTW and GM was more productive and sustainable than sole peanut.